RAPID DETERMINATION OF INDOOR AIR CONTAMINANTS IN SHOE SHOPS USING PHOTOIONIZATION DETECTORS - BOCOȘ-BINȚINȚAN, Victor; SMOLENSCHI, Alina; RAŢIU, Ileana-Andreea (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Recently, indoor air quality (IAQ) has become a serious concern. More and more people are facing health problems due to the poor air quality at the workplace; most of them are exposed to pollutants without even realizing it. Therefore, it is important to monitor the indoor air quality to prevent an unsafe environment. In the shoe making process, various volatile compounds – like toluene, found especially in adhesives – are used. These chemicals tend to slowly desorb from the final products and to accumulate ultimately inside the shoe shops. We report here the total volatile organic compounds (tVOCs) that are prone to be ionized by the UV radiation; measurements were performed over eight weeks inside six shoe shops located in Cluj-Napoca, Romania, with a ppbRAE Plus instrument manufactured by RAE Systems Inc. USA. We found with this ultra-sensitive photoionization detector (PID) maximum concentrations up to 7 ppmv of tVOCs (isobutene units) in air for each shoe shop investigated. The obtained results demonstrate that people working in the selected shoe stores may be exposed to significant tVOCs concentrations during a working day. Thus, PID devices are useful tools for quickly surveying the indoor air quality.